A grief to bury : memories of love, work & loss - Kannabiran, Vasantha (Orient BlackSwan, 2011)
A Grief to Bury: Memories of Love, Work and Loss is a series of conversations with women about marriage and widowhood. The women speak here with frankness and candour about their often quite unconventional relationships with their husbands, and of coming to terms with the loss of a life-long partner. Despite the grief, despite an altered and often fractured sense of self, each woman is determined to live a productive and creative life. Reflecting the social history of a class of women born before Independence, this volume explores how the institution of marriage shaped their lives. These are extraordinary women, who have lived rich, full lives where work has not been separated from leisure, nor has the private world of home and family been separated from the wider world of work and social commitment. As such they have redefined marriage and family, and equally the public sphere of work to make both inclusive spaces. This collection of interviews raises important questions: Is it possible to retain your identity and hold on to your beliefs in a long marriage? What is the line that separates and insulates home and family from community and nation? How do these women breathe normally and smile graciously while coping with a shock that uproots and erases chunks of the self? What happens when a long and supportive partnership ends? Eminent personalities, among them, Neera Desai, Meenakshi Mukherjee, Ela Bhatt, K. Saradamoni and Shanta Rameshwar Rao discuss their long partnerships of shared visions and love. Their choices, their struggles, and their indomitable will may provide answers to countless young people today. Apart from a general readership, this book will also appeal to students and scholars of sociology and gender studies.